2023
DOI: 10.3389/fcvm.2023.1168339
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible factor activation promotes osteogenic transition of valve interstitial cells and accelerates aortic valve calcification in a mice model of chronic kidney disease

Abstract: IntroductionValve calcification (VC) is a widespread complication in chronic kidney disease (CKD) patients. VC is an active process with the involvement of in situ osteogenic transition of valve interstitial cells (VICs). VC is accompanied by the activation of hypoxia inducible factor (HIF) pathway, but the role of HIF activation in the calcification process remains undiscovered.Methods and resultUsing in vitro and in vivo approaches we addressed the role of HIF activation in osteogenic transition of VICs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…It is increasingly clear that hypoxia and HIF‐1 activation are involved in the osteogenic phenotype switch and calcification of VSMCs and VICs (Balogh et al, 2019; Csiki et al, 2023; Mokas et al, 2016; Tóth et al, 2022). In accordance with that here, we showed that calcification of HuLECs is attenuated in the absence of HIF‐1α or HIF‐2α, suggesting that hyperglycaemia‐induced stabilisation of HIF‐1α and HIF‐2α and subsequent activation of the HIF‐1 pathway plays a critical role in HG‐induced promotion of calcification (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is increasingly clear that hypoxia and HIF‐1 activation are involved in the osteogenic phenotype switch and calcification of VSMCs and VICs (Balogh et al, 2019; Csiki et al, 2023; Mokas et al, 2016; Tóth et al, 2022). In accordance with that here, we showed that calcification of HuLECs is attenuated in the absence of HIF‐1α or HIF‐2α, suggesting that hyperglycaemia‐induced stabilisation of HIF‐1α and HIF‐2α and subsequent activation of the HIF‐1 pathway plays a critical role in HG‐induced promotion of calcification (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that HG induces HIF-1α stabilisation in LECs (Han et al, 2015) and because HIF pathway activation was shown to be associated with the promotion of vascular and valve calcification (Balogh et al, 2019;Csiki et al, 2023;Mokas et al, 2016), we next investigated whether this mechanism is involved in the HG-induced promotion of calcification in HuLECs. To address this, we treated HuLECs with OM (2.5 mmol/L Pi, 0.3 mmol/L Ca, 48 h) under NG and HG conditions.…”
Section: Hg Induces Hif Signalling and Promotes Calcification Of Hule...mentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoxia within the vascular microenvironment can trigger signaling cascades that contribute to the differentiation of VSMCs toward a chondrogenic phenotype [ 59 ]. The mechanisms underlying VSMC calcification under hypoxic conditions require either hypoxia-inducible factor (HIF) activation or the production of mitochondrial-derived reactive oxygen species (ROS) [ 60 , 61 ]. High levels of inorganic phosphate (Pi) increase VSMC migration and calcification and are related to impaired Pi/calcium balance and miR-223 involvement, whereas TGF-β/Smad3 signaling plays an inhibitory role in Pi-induced VSMC calcification [ 62 , 63 , 64 ].…”
Section: Cellular Players In Vascular Calcificationmentioning
confidence: 99%